Diastereomerically Pure Morita–Baylis–Hillman (MBH) Acetates and Carbonates from Allenic α- and γ-MBH Alcohols - Selig, Philipp; Nghiem, Tai-Lam (Synlett, 2015)
Diastereomerically pure allenic Morita–Baylis–Hillman (MBH) acetates and carbonates have been prepared from their corresponding α- and γ-MBH alcohols. Derivatizations proceeded under standard conditions without epimerization. Both α- and γ-MBH derivatives were shown to be suitable substrates for further transformations.
Keywords: allenes; catalysis; nucleophiles; protecting groups; esterification